A influência da orientação analítica nos atributos de valor percebidos pelo cliente : um estudo no setor supermercadista - Dias, Franciely Morais (2017)
The literature has demonstrated the strong relationship between the analytical orientation of organizations and the generation of competitive advantage for the same organizations (KIRON et al., 2011; KIRON, FERGUSON AND PRENTICE, 2013). Therefore, this st